PENERAPAN MODEL TIPE GROUP INVESTIGATION (GI) UNTUK MENINGKATKAN AKTIVITAS BELAJAR SISWA DAN HASIL BELAJAR MATEMATIKA MATERI SPLDV - Maria Magdalena Noi Bupu; Stefanus Notan Tupen; Maria Fatima Mei (Program Studi Pendidikan Matematika, 2023)
This study aims 1) to find out the learning activities of students in class X UPW SMKN 1 Ende on the subject matter of a system of two-variable linear equations (SPLDV) through a group investigation (GI) cooperative learning model; 2) To find out the increase in student learning outcomes a material system of two-variable linear equations (SPLDV) in class X SMKN 1 UPW Ende through the group investigation (GI) cooperative learning model. The type of research used is Classroom Action Research (PTK) with data collection techniques namely observation and tests. The learning process is carried out in stages, namely the planning stage, the action stage, the observation stage, and the reflection stage. A series of stages is called a cycle. This research occurred in 2 cycles with the same implementation stages. The results showed that student learning activities and teacher activity in learning mathematics using the group investigation cooperative model can be seen in the results of the evaluation of the first cycle and the percentage of student activity greatly increased where in the first cycle the percentage of students was 52% and in the second cycle the percentage of students reached 83%. As for teacher activity in cycle I with a percentage of 55% and in cycle II it reached 81%. Thus the GI-type cooperative model can be used in SPLDV materials.